FRCM strengthening of clay brick walls for out of plane loads. (1st October 2019) - D'Ambra, Claudio; Lignola, Gian Piero; Prota, Andrea; Fabbrocino, Francesco; Sacco, Elio
Abstract: The present work deals with the analysis of unreinforced and FRCM reinforced masonry walls subjected to out-of-plane loading. In particular, numerical simulations of full scale experimental clay brick walls, previously tested, are developed. The out of plane behaviour is relevant not only for flat walls, but also for curved structures, like as domes and vaults, for which FRCM demonstrated to be highly effective in improving their structural behaviour. In this paper, two tested walls are numerically analysed. The first wall has been tested in an unreinforced configuration inducing a significant damage distribution; then, it has been retrofitted by FRCM and tested again. The second wall has been reinforced without pre-damage and tested applying the same loading history adopted for the first wall. This allowed to remark the effect of retrofitting to damaged and undamaged walls. Both the walls were constrained on two consecutive sides and loaded by a pointwise force orthogonal to the wall mid-plane, applied at the top free corner inducing a biaxial behaviour. The numerical simulations are developed performing nonlinear three-dimensional (3D) FE analyses to clearly remark the potential benefits of the strengthening technique involving FRCM systems on the out of plane behaviour. On the basis of a micro-modelling approach, bricks and equivalent interfaces were modelled separately assigning the nonlinearity only to equivalent interface. In fact, experimental testes demonstrated that the cracking and failure localize in the mortar joints. The FRCM system was modelled by means of an equivalent layer bonded on one side of the wall through interfaces. A parametric analysis is performed on the mechanical properties of the interface to investigate on the influence of these parameters on the wall response. This allowed to discuss the main parameters governing the out-of-plane behaviour of such masonry walls.